2017
DOI: 10.3389/fpls.2017.02190
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Loci for Yield-Related Traits in Maize Revealed by a Combination of MetaQTL Analysis and Regional Association Mapping

Abstract: Maize grain yield and related traits are complex and are controlled by a large number of genes of small effect or quantitative trait loci (QTL). Over the years, a large number of yield-related QTLs have been identified in maize and deposited in public databases. However, integrating and re-analyzing these data and mining candidate loci for yield-related traits has become a major issue in maize. In this study, we collected information on QTLs conferring maize yield-related traits from 33 published studies. Then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 50 publications
7
50
0
Order By: Relevance
“…Furthermore, for MAS to be more efficient than phenotypic selection, several requirements are bound to the used QTL. These criteria pertain to the precision of the positions and the genotypic effects of the QTL, and the QTL explaining a sufficient portion of the genotypic variance, yet most of the QTL detected fall short of these prerequisites (Utz et al, 2000 ; Chen et al, 2017 ). Besides, some QTL go undetected due to their small size in the populations under consideration (Bohn et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, for MAS to be more efficient than phenotypic selection, several requirements are bound to the used QTL. These criteria pertain to the precision of the positions and the genotypic effects of the QTL, and the QTL explaining a sufficient portion of the genotypic variance, yet most of the QTL detected fall short of these prerequisites (Utz et al, 2000 ; Chen et al, 2017 ). Besides, some QTL go undetected due to their small size in the populations under consideration (Bohn et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of these, four QTL clusters were specific for high‐density treatment and 16 genomic regions contained overlapping QTLs for different traits under low and high planting densities. Ten QTL clusters (QC1‐2, QC2‐1, QC3‐5, QC6‐2, QC6‐3, QC7‐2, QC7‐5, QC9‐1, QC9‐3 and QC10‐1) overlapped with meta‐QTLs presented by Chen et al () (Table ), and these meta‐QTLs were associated with grain yield, ear‐related traits and/or kernel‐related traits. Two QTLs at bin 5.04 shared the genomic region (QC5) for EL and KNPR across both densities, and this locus also overlapped with a pleiotropic region for EL and CWPE across low and high densities, RN under low density and KNPR under high density according to Guo et al ().…”
Section: Discussionmentioning
confidence: 71%
“…The cluster QC3‐1 for KW and RN under high planting density and QJRN3 for RN in the F 2:3 families derived from the same cross were mapped in the same position (Liu et al, ), and this cluster also co‐located with the genomic region that affected CWPE and ED under low‐ and high‐density conditions (Guo et al, ). QC9‐1 had an effect on CWPE (LD), CD (LD, HD) and ED (HD), co‐mapped with QJCD9 for CD in the F 2:3 families from the same parents (Liu et al, ) and MQTL‐63 for grain yield, ear‐related traits and kernel‐related traits reported by Chen et al (). Moreover, QC9‐2 for ED and RN under low density was found in the F 2:3 generation from the same cross (Liu et al, ).…”
Section: Discussionmentioning
confidence: 80%
“…Numerous studies have been devoted to the dissection of the genetic bases regulating maize kernel size and shape. Quantitative trait loci (QTLs) analyses have mapped hundreds of QTLs for kernel‐related traits, including kernel length, kernel width, kernel thickness and hundred‐kernel weight (HKW), using various genetic populations (Chen et al ., , ; Jiang et al ., ; Li et al ., ; Liu et al ., ; Martinez et al ., ; Peng et al ., ; Tang et al ., ). A recent study identified nine QTLs related to KM using a triple testcross population (Jiang et al ., ).…”
Section: Introductionmentioning
confidence: 99%